Effects of Exercise during Weight Loss Maintenance on Appetite Regulation in Women. Issue 12 (2020) - Foright, Rebecca; Halliday, Tanya M.; Melanson, Edward L.; Hild, Allison; Legget, Kristina T.; Tregellas, Jason R.; Cornier, Marc-Andre
Abstract : ABSTRACT: Exercise is accepted as a method to improve weight loss maintenance; however, the mechanisms by which this occurs have yet to be elucidated. In this pilot study, 13 women with obesity underwent a structured weight loss program (goal 8%–10% weight loss) and were then randomized to either a 12-wk diet ( n = 7) or an aerobic exercise training ( n = 6) intervention aimed at maintaining weight loss. At baseline, post–weight loss, and following the weight loss maintenance interventions, measurements of appetite (hunger and satiety) and appetite-regulating hormones (leptin, ghrelin, peptide tyrosine tyrosine, and glucagon-like peptide 1) were obtained after an overnight fast and for 3 h after a standardized test meal. Ad libitum energy intake was measured at a lunch meal. During the weight loss phase, participants lost 9.1% ± 1.1% of baseline body weight. Participants in both groups maintained weight loss during the 12-wk weight loss maintenance intervention. No differences in fasting leptin ( P = 0.68) or in ghrelin ( P = 0.30), peptide tyrosine tyrosine ( P = 0.93), and glucagon-like peptide 1 ( P = 0.98) area under the curve were detected between groups. Similarly, ratings of hunger ( P = 0.99) and satiety ( P = 0.65) area under the curve after the standardized test meal also did not differ between the groups nor did ad libitum energy intake at lunch. In summary, the 12-wk diet and exercise interventions were equally effective at maintaining weight loss in women, and no differences in measures of appetite regulation and food intake were found.